Histopathologic Profile of Premalignant and Malignant Lesions of Gallbladder - Goyal, Binita (Journal of College of Medical Sciences-Nepal, 2021)
Introduction: Neoplastic lesions of gallbladder are less well defined than other lesions in gastrointestinal tract due to rarity of lesions and also poor accessibility of this site. More than fifty percent cases of cancer are clinically missed. This study was aimed to see the histopathologic spectrum of premalignant and malignant lesions, compare clinical diagnosis with histopathological diagnosis and see association between gross morphology and missed clinical diagnosis. Methods: This study was conducted on 56 consecutive cases of premalignant and malignant lesions of gallbladder received in study period of 10 years from January 2011 to December 2020. Results: Age of the patients ranged from 13 – 84 years with a mean±SD of 56.8±13.7 years with maximum 17 (30.4%) cases in 41 – 50 years age group. There were 14 (25.0%) males and 42 (75.0%) females with a male female ratio of 1:3. 10 (17.9%) cases were premalignant lesions and 46 (82.1%) cases were malignant lesions. 93.5% malignant cases were adenocarcinoma. 41.3% cases were clinically not suspected to be malignant. There was no association between gross morphology and missed clinical diagnosis (p > 0.05). Conclusions: Routine histopathologic examination of all the resected gallbladder specimens is manadatory as important diagnosis can be missed.